Stimuli-responsive nanomaterials: Innovations in on-demand drug release systems (Asian Journal of Pharmaceutics (AJP), 2025)
Stimuli-responsive nanoparticles (SRNs) provide an innovative method in pharmaceuticals, facilitating accurate,on-demand drug release systems customized for particular therapeutic requirements. These sophisticated materialsreact to internal (pH, enzymes, and redox potential) or exterior (temperature, light, and magnetic fields) stimuli,enabling regulated drug release while reducing adverse effects. Recent developments in the design and engineeringof SRNs have improved their sensitivity, biocompatibility, and drug-loading efficiency, rendering them optimalcandidates for customized therapy. Notwithstanding their potential, issues related to stability, possible cytotoxicity,and scalability impede their clinical application. Contemporary research emphasizes surmounting these obstaclesusing multistimuli-responsive systems and the use of developing technologies such as artificial intelligence. Thisreview elucidates the processes, material developments, and pharmacological applications of SRNs, addressessignificant limits, and examines prospective avenues for their advancement. By tackling these issues, SRNspossess the capacity to revolutionize contemporary drug delivery methods, providing unparalleled precision andefficiency in therapeutic treatments.